Digital Transformation Leadership in Elementary School Management: Evidence from a Digital School Transformation Program - Isep Djuanda; Sri Andriyani (Al-Qalam Institue, 2026)
This study aims to examine the role of digital transformation leadership in strengthening elementary school management and improving educational quality. The research employed a qualitative approach using a systematic literature review combined with a case study to explore leadership practices, challenges, and strategies for implementing digital transformation in primary education. The findings reveal that effective digital transformation leadership depends on the integration of a clear strategic vision, digital competencies, and an adaptive organizational culture. School leaders play a pivotal role in promoting technology adoption, enhancing teachers’ digital capacity, fostering collaboration, and establishing a sustainable digital learning ecosystem. Furthermore, continuous professional development and stakeholder engagement are essential for ensuring the successful implementation of digital initiatives. The study implies that educational institutions should develop a contextual digital leadership model that prioritizes human resource development as the foundation for sustainable digital transformation and improved educational management. Such a model can support schools in responding effectively to technological change while enhancing organizational performance and learning quality.